Bridging East and West: A Comparative Study of Pragmatism of Ibn Khaldun and John Dewey in the Philosophy of Education - Pratiwi, Risa; Hidayat, Fahri; Siswadi, Siswadi (J-PAI: Jurnal Pendidikan Agama Islam, 2025)
This study is motivated by contemporary challenges in adaptive and context responsive Islamic Education. This research aims to analyze and compare the educational philosophies of John Dewey and Ibn Khaldun as a basis for developing such a model. Although John Dewey and Ibn Khaldun both emphasize that knowledge must have practical implications and be based on real experiences, research linking their ideas in the context of contemporary Islamic education reform remains limited. Therefore, a comparative analysis is needed to provide a conceptual basis for the renewal of Islamic education in the modern era. This study uses a qualitative approach with a comparative study of the two figures and relevant academic literature. The results of the analysis show that Dewey and Ibn Khaldun have major conceptual similarities, both criticize purely theoretical education and emphasize experiential and practice-based learning as the foundation of meaningful education. Dewey viewed education as a means of continuous social reconstruction as well as a way to shape democratic citizens. Meanwhile, Ibn Khaldun sees education as the foundation for moral formation, social welfare, and the advancement of civilization. The fundamental difference between the two lies in their philosophical foundations. Dewey's thinking is built on secular rationalism and democratic values, while Ibn Khaldun's ideas stem from Islamic moral and spiritual values. The integration of their two schools of thought provides a new framework for the development of an Islamic education paradigm that is pragmatic, contextual, and oriented towards social change. This research also enriches the discourse on Islamic education by connecting the ethical-spiritual dimensions and the practical needs of today's society.